PTU-060 Iron deficiency anaemia in plain sight at the front door in the midlands. Issue 2 (June 2019) - Thumbe, Akanksha; Quraishi, Mohammed Nabil; Dabhi, Kevalben; Sharma, Neel; Sharma, Naveen; Lasserson, Daniel; Iqbal, Tariq; Bhala, Neeraj
Abstract : Background: Iron deficiency anaemia (IDA) can be a marker of serious underlying disease, particularly in the older population due to its association with GI malignancy. Guidelines published by the British Society of Gastroenterology (BSG) recommend that all patients with IDA should be screened for coeliac disease and that dual endoscopy should be considered in all men and postmenopausal women. Aims: To determine adherence to these guidelines, we conducted a retrospective audit of all patients admitted to the Clinical Decision Unit at the Queen Elizabeth Hospital Birmingham between April 1st 2017 and March 31st 2018. Methods: Data obtained from informatics and the electronic prescribing system was analysed to quantify: (1) the proportion of patients with microcytic anaemia who had a ferritin test, (2) those with IDA who had IgA tTG measured and (3) those who had OGD and colonoscopy/CT colonoscopy requested. Results: In the study period, 6, 047 (41%) of 14, 562 patients were anaemic with 1, 237 (8%) specifically having a microcytic anaemia. Of these, 407 (40%) had ferritin measurements which found that 171 (42%) had IDA (ferritin <30 µg/ml). This cohort was comprised of 33 premenopausal women, 84 postmenopausal women and 54 men. 54 (32%) were tTG screened, 30 (56%) men had an OGD and 17 (35%) had a colonoscopy compared to 26 (31%) postmenopausal women having an OGD and 24 (29%) having colonoscopy/CT colonoscopy. Conclusions: In patients presenting acutely, IDA is common, yet often overlooked. A minority of patients were investigated in line with the BSG guidelines demonstrating a need for improved awareness of investigation of IDA among those caring for acutely ill patients.